How trust in coworkers fosters knowledge sharing in virtual teams? A multilevel moderated mediation model of psychological safety, team virtuality, and self-efficacy - Hao, Qi; Zhang, Bin; Shi, Yijun; Yang, Qizhong (Frontiers in Psychology, 2022)
Examining the influence of trust in fostering knowledge sharing behavior (KSB) in virtual teams is of great research value in the current complex, dynamic, and competitive era of a knowledge economy. This study investigated the relationship between trust in coworkers (TC) and KSB. Based on social information processing theory and social cognitive theory, we developed a multilevel moderated mediation model where the team members’ psychological safety (PS) was considered a mediator, while team virtuality (TV) and knowledge sharing self-efficacy (KSSE) acted as team and individual-level moderators, respectively. On surveying 282 individuals in 37 virtual teams of three Chinese internet companies, we found that TC positively affected team members’ KSB and this relationship was fully mediated by team members’ PS. Our findings also demonstrated that the effect of TC on KSB depended on the degree of TV and employees’ KSSE. Specifically, when TV and KSSE were higher, the TC–PS and PS–KSB relationship and the mediating effects of PS in the TC–PS–KSB relationship were all stronger. Our study extends the trust-KSB literature by identifying the psychological mechanism and boundary conditions in the TC-KSB relationship. Moreover, our findings also offer valuable managerial implications for virtual team managers on facilitating team members’ PS and KSB.